The Effectiveness of a Character Education-Based Daily Mutaba'ah Journal Book on the Independence of Elementary School Students - Nugraha, Irwan; Yarmi, Gusti; Suhandoko, Astri Dwi Jayanti (Syntax Corporation, 2026)
The background of this study is based on the weakness of students’ independent character, which is caused by learning practices that remain oriented toward cognitive aspects and the lack of systematic and collaborative character habituation media between schools and parents. This study aims to examine the effectiveness of the Mutaba‘ah Yaumiyah Book based on character education in improving elementary school students’ independence. The study employed a Research and Development (R&D) approach using a modified Borg and Gall model, focusing on the product effectiveness testing stage. The research subjects were upper-grade students at SDIT Ulil Albab Batam. The research instrument used was an observation rubric for independent character development, and data analysis was conducted using a one-sample t-test. The results showed that the calculated t-value was 22.91, which was higher than the t-table value of 1.895, with a significance level of p < 0.05. These findings indicate that the Mutaba‘ah Yaumiyah Book based on character education is effective in improving elementary school students’ independence. This book can serve as an applicable and sustainable medium for character development in integrated Islamic elementary schools.